Exchange Rate Pass-through in a Small Open Economy: The Importance of the Distribution Sector - Pål Boug; Ådne Cappelen; Torbjørn Eika (Statistics Norway, Research Department, 2005)
Several small open economies switched to inflation targeting during the 1990s, thereby giving up various forms of exchange rate targeting in favour of flexible exchange rates. Norway did the same early in 2001, and has thereafter experienced highly varying nominal exchange rates with consumer price inflation dropping far below the target during 2003 and 2004. Knowledge of the degree of exchange rate pass-through to import prices and further to consumer prices is essential for inflation targeting. The literature suggests that pass-through is greater to import prices than to consumer prices, which presumably is related to the role of distributors in the economy. We present empirical evidence on these issues for Norway by estimating import price equations and a dynamic model of the distributors pricing behaviour. Using a large-scale macroeconometric model of the Norwegian economy, we find exchange rate pass-through to import prices to be quite rapid in the short run, while pass-through to consumer prices seems to be modest. We show that, among the numerous channels through which the exchange rate operate, trade margins in the distribution sector act as cushions to exchange rate fluctuations, thereby being one of the main important source for the delay in pass-through. In spite of moderate pass-through to consumer prices, we find inflationary effects of exchange rate changes even in the short run, an insight important for inflation targeting central banks.
Keywords: C51; C52; E31; F31; 330; Exchange rate pass-through; pricing behaviour; the distribution sector; econometric modelling and macroeconomic analysis